Cosmic Ray Physics with the LOFAR Radio Telescope. (February 2019) - Winchen, T; Bonardi, A; Buitink, S; Corstanje, A; Falcke, H; Hare, B M; Hörandel, J R; Mitra, P; Mulrey, K; Nelles, A; Rachen, J P; Rossetto, L; et al.
Abstract: The LOFAR radio telescope is able to measure the radio emission from cosmic ray induced air showers with hundreds of individual antennas. This allows for precision testing of the emission mechanisms for the radio signal as well as determination of the depth of shower maximum X max, the shower observable most sensitive to the mass of the primary cosmic ray, to better than 20 g cm −2 . With a densely instrumented circular area of roughly 320 m 2, LOFAR is targeting for cosmic ray astrophysics in the energy range 10 16 –10 18 eV. In this contribution we give an overview of the status, recent results, and future plans of cosmic ray detection with the LOFAR radio telescope.